KUALITAS SUMBER DAYA MANUSIA (Kualifikasi, Kompetensi dan Sertifikasi Guru) - Sunhaji Sunhaji (Institut Agama Islam Negeri Purwokerto, 2014)
One of the characteristics of today's globalization era is that there are various competition in people's life. The globalization era is marked by a variety of scientific progress and the success of technology. The globalized world gives a challenge for people who can compete and deal with it, other wise it can become a threat to those who are not ready to deal with it. The era of globalization is one of the advantages for educated human resources. Education as one of the main pillars of human resource development will be the benchmark for excellence of human resources. A teacher is one of the main pillars for human resource development, without which the education process will not run. Efforts to improve human resources, especially teachers, are mainly by increasing their competences, qualifications and certification of educations. Improving teachers' qualification, competencies and certification of education is a â€œcondicio sine qua nonâ€ or an indispensable and essential action for the Indonesian government.Â Salah satu ciri era global seperti sekarang ini adalah kompetisi dalam berbagai kehidupan, dengan ditandai oleh berbagai kemajuan ilmu pengetahuan dan teknologi.Iindividu yang sukses adalah yang dapat bersaing dengan dunia global sehingga era global merupakan tantangan dan sekaligus ancaman bagi mereka yang tidak siap menghadapinya. Salah satu bekal untuk menghadapainya adalah sumber daya manusia yang unggul. Pendidikan sebagai salah satu pilar utama pengembangan SDM akan menjadi tolok ukur sebuah keunggulan SDM. Guru adalah salah orang yang utama dan pertama sebagai pilar peningkatan SDM, tanpa guru proses pendidikan tidak akan berjalan. Upaya peningkatan SDM terutama guru adalah dengan melalui peningkatan kualifikasi dan kompetensi serta sertifikasi pendidik. Peningkatan kualifikasi, kompetensi serta sertifikasi pendidik adalahmerupakan condition sine quanon atau suatu kefardhuan Nasional bagi bangsa Indonesia.